The Effectiveness of Kombucha as a Starter in the Production of Fermented Milk Beverages - Ningtiyas, Weny Dwi; Irfan, Muhammad; Mukhlisah, Andi Nurul; Syah, Setiawan Putra; Rab, Samsu Alam; Mutmainna, Andi (Jurnal Agripet, 2025)
A symbiotic culture of kombucha (SCOBY) has the potential to act as a probiotic source of lactic acid bacteria, which can be combined with fermented beverage starters using fresh or reconstituted milk as a medium. This study aims to evaluate the effectiveness of kombucha in producing fermented milk products with microbiological characteristics. The experimental design used was a completely randomized factorial design with two treatment levels: skim milk concentration and kombucha concentration. The parameters observed included total lactic acid bacteria, pH, and total lactic acid. Data were analyzed by ANOVA using IBM SPSS Statistics program 29, and if significant effects were found, Duncan's post-hoc test was conducted. The results showed that using kombucha as a starter had a very significant effect (P0.01) on all three variables observed. The amount of lactic acid bacteria (LAB) in the fermented milk met the SNI standard, with a concentration of 7 log CFU/ml. It can be concluded that kombucha can be used as a starter in fermented milk production. Although the percentage of lactic acid levels and pH values are not yet listed in the Indonesian National Standard, both pH value and lactic acid levels showed a very significant effect. A higher percentage of kombucha starter led to higher lactic acid content, which is a result of bacterial metabolism. Additionally, a higher percentage of kombucha starter resulted in a lower pH value in the kombucha-fermented milk.